Work or welfare after cancer? Explorations of identity and stigma. Issue 8 (3rd July 2015) - Moffatt, Suzanne; Noble, Emma
Abstract: With increasing numbers of people living with cancer, a greater focus is required on the social consequences of the disease. This article explores the connections between cancer and employment and the constraints imposed by ill health and wider structural conditions. Narrative data from 23 people of working age with cancer in north‐east England collected longitudinally over 16 months highlight the impact of financial strain caused by temporary or permanent interruption to employment, and the positive benefits of an upstream welfare rights intervention in enabling participants to claim benefit entitlements and boost incomes. Returning to work, for those who were able, helped repair the disruption caused by the illness. For those unable to work, reliance on welfare benefits, while necessary, conferred a stigmatised identity that compounded the disruption wrought by cancer. While stigma occurs at the individual level, the structural dimensions of stigma need to be acknowledged in order to analyse the forces that cause, maintain and perpetuate the stigma associated with claiming welfare while ill. We conclude that current UK policies and welfare reforms to reduce sickness‐related welfare claims will lead to greater hardship during periods of ill health and increase inequalities.